Click, Clack, Moo Cows That Type - Cronin, Doreen; Nang ChanYeema (Hong Kong Simon & Schuster Books for Young Readers, 2000)
When Farmer Brown's cows find a typewriter in the barn they start making demands and go on strike when the farmer refuses to give them what they want.
Keywords: Story Collection